The climate change and agriculture – dimensions and correlations - Matei, Mirela; Stancu, Adrian; Vuković, Predrag (Applied Studies in Agribusiness and Commerce, 2010)
Global climate changes are taking place and its impacts on economy are already occurring in fields like tourism, agriculture, forestry, infrastructure, insurance industry or capital market. Specialists draw attention that climate change has negative effects and positive effects. For example, in some parts of Europe, especially in north, the agricultural may benefit from temperature rise increasing carbon dioxide levels in the atmosphere. The most important part of these changes is due to greenhouse gas (GHG) emissions from human activity. Between greenhouse gases, carbon dioxide (CO2) is the largest contributor with a weight around of 80% of total GHG emissions. The agriculture is the most affected sector by the climate change, but agricultural activities have many negative implications on environment through emissions of methane and nitrous oxide that result from changes in land use. Besides the negative impact, the agriculture may play a positive role to environment protection through the production of bio fuels. Because of the huge implications of climate change on human activities, the public authorities have made important steps in order to control this phenomenon, to reduce and prevent the negative impact.